INVESTIGATION OF HYDROCHEMICAL DYNAMICS OF GROUNDWATER IN COASTAL BLOCKS OF TIRUVALLUR DISTRICT, TAMILNADU, INDIA - GEETHA SUBBIAH; SUNIL J; DHARMENDIRA KUMAR M (Journal of the Chilean Chemical Society, 2021)
This paper presents the behaviour of cation and anion in samples of water collected from the coastal blocks of Tiruvallur District, Tamilnadu, India. 13 physiochemical parameters are investigated on the uniformly collected groundwater samples. It is revealed that fifty percentage of groundwater samples surpassed water quality levels pertaining to drinking and irrigation. In this investigation, descriptive statistical analysis is performed to understand groundwater characteristics. The hydrochemical dynamics of groundwater are evaluated using graphical plots Piper, Wilcox, and Gibbs. Through the Piper plot, it is concluded that high concentrations of sodium would induce cation exchange between Ca2+ and Mg2+ from the soil. This may lead to the acceleration of air and water circulation through the soil in wet conditions. The inference of the Piper plot is supported by end result of Gibbs plot. Gibbs plot indicates evaporation dominance of anthropogenic activities, while Wilcox plot clearly indicates groundwater's suitability for irrigation purposes. Moreover, the cation concentration is seen to be high on the eastern portion of the chosen area. The level of groundwater treatment should be adequately determined for potable purposes and for agricultural purposes as the study concludes the intrusion of saline water, rock water interaction and irrigation flows.